2015
DOI: 10.1016/j.fuproc.2015.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Deposit build-up and ash behavior in dual fluid bed steam gasification of logging residues in an industrial power plant

Abstract: A promising way to substitute fossil fuels for production of electricity, heat, fuels for transportation and synthetic chemicals is biomass steam gasification in a dual fluidized bed (DFB). Using lower-cost feedstock, such as logging residues, instead of stemwood, improves the economic operation. In Senden, near Ulm in Germany, the first plant using logging residues is successfully operated by Stadtwerke Ulm. The major difficulties are slagging and deposit build-up. This paper characterizes inorganic component… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 30 publications
2
29
0
Order By: Relevance
“…A detailed description of the feedstock was provided in a previous work [30]. Figure 2 shows the flow sheet of the DFB gasification process as it occurs in the power plant in Senden, Germany.…”
Section: Description Of the Dual Fluid Bed Steam Gasification Of Biomassmentioning
confidence: 99%
See 1 more Smart Citation
“…A detailed description of the feedstock was provided in a previous work [30]. Figure 2 shows the flow sheet of the DFB gasification process as it occurs in the power plant in Senden, Germany.…”
Section: Description Of the Dual Fluid Bed Steam Gasification Of Biomassmentioning
confidence: 99%
“…Interactions between ash components and the bed material have different consequences. The formation of layers on bed particles can result in agglomeration, slagging, and deposit buildup [25,[28][29][30][31][32]. However, calcium-rich layers have shown a significant increase of the catalytic activity of bed particles [33][34][35][36] and are therefore highly desirable for gasification processes.…”
Section: Introductionmentioning
confidence: 99%
“…The most widely used biomass in energy conversion processes is forest-derived but increasing demand increases its stock prices [1,2] and leads to the necessity to research alternative bio-based fuels. Logging residues are cheaper wood-based alternatives [3], which could be able to substitute parts or the entire logging wood used in biomass-fueled plants for heat and power production. Agricultural waste is a source of biomass that increasingly gains attention, as well as waste streams like sewage sludge and municipal waste, which behave differently to woody-based biomass and therefore need more caution when used in thermochemical energy conversion processes.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown an interaction between the bed material used in fluidized beds and ash contained in fuel. This interaction can lead to agglomerations [4,[6][7][8], deposits [3,9] and layer formation [10][11][12][13][14][15] on bed material particles. The different mechanisms dominating the particle layer formation on quartz were summarized by Brus et al [8].…”
Section: Introductionmentioning
confidence: 99%
“…However, the ash-forming matter in agricultural wastes is different in comparison to woody biomass and causes severe problems in operation, such as deposit build-up [4], slagging and bed agglomeration [5][6][7][8][9]. The latter is particularly important, since bed agglomeration may lead to total bed defluidization and as a consequence, termination of operation.…”
Section: Introductionmentioning
confidence: 99%